Refractory hyperammonemic encephalopathy in Fibrolamellar hepatocellular carcinoma: a case report and literature review - Ahmed, Arwa; Ata, Fateen; Gaber, Mohammed; Petkar, Mahir; Mahfouz, Ahmed; Schirmacher, Peter; Musa, Sara; Hashim, Ahmed (Current problems in cancer, 2022)
Fibrolamellar hepatocellular carcinoma is a rare type of hepatocellular carcinoma with unclear etiology. Its prevalence ranges from 0.6%-5%. One of the rare manifestations of FHCC includes hyperammonemic hepatic encephalopathy (HAE). Data regarding HAE in FHCC is limited to case reports, and much is unknown, including its precipitating factors, clinical course, and management. We have reported one such case of FHCC associated HAE and presented an extensive literature review on the topic. We report the case of a 26-year-old Pakistani male who was diagnosed with fibrolamellar hepatocellular carcinoma. ...